Народна медицина та її роль в традиційній культурі українців: стислий історичний екскурс - Яцентюк, Галина (Київський національний університет імені Тараса Шевченка, 2024)
Ця стаття присвячена дослідженню історичних та етнічних аспектів народної медицини в українській традиційній культурі. Вона має на меті висвітлити еволюцію цієї складної та багатошарової системи українських народних знань і практик, починаючи від Русі й до сучасності. Відтак, через призму вивчення етнічних коренів та історії народної медицини в українській традиційній культурі ми отримуємо можливість краще зрозуміти унікальність та глибину національної спадщини України.

This article is devoted to the study of historical and ethnic aspects of folk medicine in Ukrainian traditional culture. It aims to highlight the evolution of this complex and multilayered system of Ukrainian folk knowledge and practices, from Kyevan Rus to the present day. Therefore, through the prism of studying the ethnic roots and history of folk medicine in Ukrainian traditional culture, we have the opportunity to better understand the uniqueness and depth of Ukraine’s national heritage, as well as to open new horizons for further research in this area.
Traditional Medicine and Its Role in the Traditional Culture of Ukrainians: a Brief Historical Overview
Keywords: народна медицина; медицина Київської Русі; історія народної медицини в Україні; фітотерапія; національний феномен; традиція; українська культура; folk medicine; medicine of Kyevan Rus; history of folk medicine in Ukraine; phytotherapy; national phenomenon; tradition; Ukrainian culture